2010
DOI: 10.1103/physreve.82.021101
|View full text |Cite
|
Sign up to set email alerts
|

Memory-induced anomalous dynamics: Emergence of diffusion, subdiffusion, and superdiffusion from a single random walk model

Abstract: We present a random walk model that exhibits asymptotic subdiffusive, diffusive, and superdiffusive behavior in different parameter regimes. This appears to be the first instance of a single random walk model leading to all three forms of behavior by simply changing parameter values. Furthermore, the model offers the great advantage of analytic tractability. Our model is non-Markovian in that the next jump of the walker is (probabilistically) determined by the history of past jumps. It also has elements of int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 22 publications
(29 reference statements)
6
85
0
1
Order By: Relevance
“…(27). Consistently with the analysis, each curve (for ∆ < t) can be very well fitted by the approximation (32), that is, a linear behavior in ∆ is observed. In Fig.…”
Section: A Asymptotic Randomnesssupporting
confidence: 81%
See 2 more Smart Citations
“…(27). Consistently with the analysis, each curve (for ∆ < t) can be very well fitted by the approximation (32), that is, a linear behavior in ∆ is observed. In Fig.…”
Section: A Asymptotic Randomnesssupporting
confidence: 81%
“…It is known that globally correlated stochastic dynamics lead to anomalous diffusion processes [27][28][29][30][31][32][33][34][35]. On the other hand, we remark that the interplay between memory effects and weak ergodicity breaking was study previously such as for example in correlated continuous-time random walk models [36,37], single-file diffusion [38], and fractional Brownian-Langevin motion [39].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Due to its simpleness, the microscopic memory effect, the key origin of anomalous diffusion, was easily applied to other models, among which Cressoni et al suggested that the loss of recent memory rather than the distant past can induce persistence, which is related to the repetitive behaviors and psychological symptoms of Alzheimer's disease [30]. In [31], it was shown that, by adding a possibility that a walker does not move at all in the model of [29], diffusive, superdiffusive, and subdiffusive behaviors can exhibit in different parameter regimes. It has the advantage to describe the anomalous diffusion within a single model just by changing the parameters; however, in this case, the subdiffusive property may be caused by the staying behavior rather than the memory effect and thus superdiffusion and subdiffusion are not induced by a single origin.…”
Section: Introductionmentioning
confidence: 99%
“…In general, systems of different nature reveal asymptotically different modes of anomalous diffusion: either subor superdiffusion. 16 Only one example of a system showing anomalous as well as normal diffusion as an asymptotic state is described so far in the literature, a formal random walk model with a multi-parametric memory, 17 which, however, is too complicated to gain more insight into the physics of anomalous diffusion.…”
Section: Introductionmentioning
confidence: 99%